IMPACT OF INCOME ON INTEREST IN ARABIC COFFEE FERMENTATION IN SUMBERWRINGIN BONDOWOSO SUB-DISTRICT - Saenal Mustafa; Tanti Kustiari; Ridwan Iskandar (ITScience (Information Technology and Science), 2023)
The fermentation process determines the quality of coffee beans in terms of color, taste and aroma. One of the problems is the low quality of coffee beans. This is caused by the low interest of farmers who carry out fermentation in accordance with Standard Operating Procedures. Farmers' interest is influenced by several factors, one of which is the income received by coffee farmers. This study examines the effect of income on farmers' interest in fermenting Arabica coffee. The variables used in this study are income and farmers' interest in fermenting in accordance with the applicable SOPs on Geographical Indications of java arabica coffee ijen raung. The location was purposively selected in Sumberwringin Subdistrict with the consideration that the area is the main producer of coffee. The research sample was 103 farmer group members selected by simple randomization. The method used was descriptive quantitative. Data analysis using simple linear regression with the help of SPSS. The results showed that the amount of income had a significant effect on farmers' interest in doing the coffee fermentation process with a significance value of 0.040. While the rest is influenced by other factors not examined in this study. Ijen Raung Arabica coffee farmers' income is at a moderate level, between 1.6 and 3.1 million rupiah. Farmers can budget part of their income to finance various needs during the coffee fermentation process.